Multiple Resonances Induced Terahertz Broadband Filtering in a Bilayer Metamaterial - Zeng, Qiuming; Huang, Yi; Zhong, Shuncong; Lin, Tingling; Zhong, Yujie; Zhang, Zhenghao; Yu, Yingjie; Peng, Zhike (Frontiers in Physics, 2022)
A bilayer metamaterial to realize the broadband transmission in a terahertz (THz) filter was proposed, whose periodic unit structure consists of two rectangular apertures. The broadband consisting of three transmission peaks has a 3dB transmission range of 0.75 THz which is 1.6 times that of monolayer structure. Different from the traditional narrow band excitation mode, two additional transmission peaks are produced by the bilayer metamaterials. Sweeping frequency analysis has illustrated that the spacing between two layers of metamaterials has an influence on these additional transmission peaks. The bandwidth ranges can be regulated by adjusting the spacing at proportional height. In particular, the experimental results show that the proposed filter has excellent frequency selective performance with a bandwidth of 0.7 THz from 0.79 THz to 1.49 THz. This design of broadband filtering by introducing the bilayer metamaterial supplies a new approach with potential application in the THz broadband filter.